(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Financial statements serve as a mirror reflecting the company's strength and weaknesses as well as its financial situation. Internally, financial statements are useful to the company's stockholders, board of directors, managers, and certain employees, including labor unions. Externally, however, they are important to potential investors, government agencies in charge of taxation and regulation, lenders like banks and credit rating agencies, investment analysts, and stock brokers. Based on the financial reports of Indian banks researcher has examined it using ratio analysis. This study attempts to investigate and analyze Indian banks' financial statements from 2018–19 to 2022–2023 utilizing ratio analysis. The study's goals were to examine the bank's profitability, short- and long-term solvency, and to provide insightful recommendations regarding the bank's financial standing. Here, ratio analysis is one of the research instruments used. Secondary data from numerous journals and websites, including Moneycontrol and Trendlyne, among others, was used in the study.